(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
Basic psychological needs are defined as internal conditions essential for continuous psychological development, integrity and well-being. They are energizing states, and their satisfaction is precondition for psychic health and well-being, while thwarting leads to ill-being. Those needs have inherent roots and their forming, manifesting and satisfaction are under strong influence by the social environment. Findings from the research show that increasing in their satisfaction is followed by increase in the level of well-being. Also, results show that essential for optimal functioning and well-being is, if satisfaction of all needs is in balance.